2022
DOI: 10.56028/aetr.3.1.65
|View full text |Cite
|
Sign up to set email alerts
|

Study on the impact of a biopolymer-fiber combination on soil reinforcement

Abstract: Due to environmental concerns, the search for eco-friendly and efficient soil reinforcement has become urgent in recent. In this paper, the low-carbon and environment-friendly materials biopolymer and fibers were used for soil reinforcement. Direct shear tests were carried out to determine the reinforcement effect, results show that the shear strength of soil increases first and then decreases with the increase of fiber content, it reaches to the peak value at the content of 0.5%. Biopolymer increases soil she… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…Fatehi et al [52] also studied the effect of the biopolymer ratio on soil strength, using sodium alginate and AGAR to improve a kaolinite-sand mixture, and found that the optimal biopolymer content was in the range of 0.5-1% (relative to the soil weight). Gu et al [53] concluded through direct shear tests on cellulose-improved soil that with the increase in the cellulose content, the shear strength of the soil first increased and then decreased, reaching a peak when the cellulose content was 0.5%.…”
Section: Effects Of Types and Ratios Of Biopolymers On The Mechanical...mentioning
confidence: 99%
“…Fatehi et al [52] also studied the effect of the biopolymer ratio on soil strength, using sodium alginate and AGAR to improve a kaolinite-sand mixture, and found that the optimal biopolymer content was in the range of 0.5-1% (relative to the soil weight). Gu et al [53] concluded through direct shear tests on cellulose-improved soil that with the increase in the cellulose content, the shear strength of the soil first increased and then decreased, reaching a peak when the cellulose content was 0.5%.…”
Section: Effects Of Types and Ratios Of Biopolymers On The Mechanical...mentioning
confidence: 99%
“…However, using cement for the purposes of soil reinforcement reduces the workability and durability of soil. In addition, it also adds detrimental effects, such as undegradable toxicity to the environmental conditions [ 8 , 9 , 10 ]. Moreover, the production of cement contributes to a large amount of greenhouse gas which, in turn, causes global warming.…”
Section: Introductionmentioning
confidence: 99%